Sequencing and de novo transcriptome assembly of Brachypodium sylvaticum (Poaceae)1. (5th March 2013) - Fox, Samuel E.; Preece, Justin; Kimbrel, Jeffrey A.; Marchini, Gina L.; Sage, Abigail; Youens‐Clark, Ken; Cruzan, Mitchell B.; Jaiswal, Pankaj
Abstract : Premise of the study: We report the de novo assembly and characterization of the transcriptomes of Brachypodium sylvaticum (slender false‐brome) accessions from native populations of Spain and Greece, and an invasive population west of Corvallis, Oregon, USA. Methods and Results: More than 350 million sequence reads from the mRNA libraries prepared from three B. sylvaticum genotypes were assembled into 120, 091 (Corvallis), 104, 950 (Spain), and 177, 682 (Greece) transcript contigs. In comparison with the B. distachyon Bd21 reference genome and GenBank protein sequences, we estimate >90% exome coverage for B. sylvaticum . The transcripts were assigned Gene Ontology and InterPro annotations. Brachypodium sylvaticum sequence reads aligned against the Bd21 genome revealed 394, 654 single‐nucleotide polymorphisms (SNPs) and >20, 000 simple sequence repeat (SSR) DNA sites. Conclusions: To our knowledge, this is the first report of transcriptome sequencing of invasive plant species with a closely related sequenced reference genome. The sequences and identified SNP variant and SSR sites will provide tools for developing novel genetic markers for use in genotyping and characterization of invasive behavior of B. sylvaticum .